Preparation of 2-Hydroxyethyl Acrylate/Acrylamide Nanocomposite Hydrogels via Controlled Frontal Photopolymerization with In Situ-Formed ZrO2 Nanoparticles - Akman, Onur; Ozcelik Kazancioglu, Elif; Mumtaz, Talha; Jockusch, Steffen; Arsu, Nergis (AMER CHEMICAL SOC, 2026)
In this study, the in situ frontal photopolymerization (FPP) of a 2-hydroxyethyl acrylate (2-HEA) and acrylamide (AAm) monomer system was efficiently carried out using bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (BAPO) as the photoinitiator, generating mechanically robust hydrogels with swelling ratios above 500% in water. The incorporation of a small amount of in situ-formed ZrO2 nanoparticles, using ZrCl4 as a nanoparticle precursor (0.5% w/w), increased the conversion of monomer to polymer and significantly enhanced the mechanical properties of the hydrogels while maintaining high swelling ratios (similar to 400%). Analysis of the FPP kinetics was performed with a video camera and thermal imaging, as well as photo-DSC. Mechanistic studies involved laser flash photolysis. The properties of the generated hydrogels were determined by swelling studies, SEM imaging, and tensile strength measurements. The in situ FPP approach enables rapid in situ well-distributed nanoparticle formation within thick hydrogels, providing a highly controllable and efficient strategy for fabricating composite hydrogels with tailored properties.
Keywords: Controlled frontal photopolymerization; In situ formationof ZrO2 nanoparticles; Hydrogels; 2-Hydroxyethylacrylate; Acrylamide; Bis(acyl)phosphine oxide; RADICAL POLYMERIZATION; PHOTOINITIATORS; REACTIVITY; MECHANISM; Materials Science; Polymer Science